Performance of magnetic resonance imaging in pulmonary fungal disease compared to high‐resolution computed tomography. Issue 4 (9th January 2017) - Sartori, Ana; Souza, Arthur; Zanon, Matheus; Irion, Klaus; Marchiori, Edson; Watte, Guilherme; Hochhegger, Bruno
Summary: To evaluate the performance of magnetic resonance imaging (MRI) compared to computed tomography (CT) in patients diagnosed with pulmonary mycosis. We prospectively included 21 patients diagnosed with pulmonary mycosis between January 2013 and October 2014. Inclusion criteria were presence of respiratory symptoms, histopathological diagnosis of mycosis and absence of mycosis treatment. Reviewers identified one predominant imaging pattern per patient: nodular, reticular or airspace pattern. Afterwards, all CT findings were analysed separately per lobe and compared to MRI. Nodular pattern was the most common found (CT: 76.20%; MRI: 80.96%), followed by airspace pattern (CT and MRI: 9.52%) and reticular (CT: 9.52%; MRI: 4.76%). Compared to CT, MRI performance varied according to radiological finding and pulmonary region. For nodules, MRI presented high sensitivity (100% [95% CI: 93.52‐100]) and specificity (100% [95% CI: 92.00‐100]). For bronchiectasis and septal thickening, there were poorer positive predictive values (33.33% [95% CI: 1.77‐87.47]; and 83.33% [95% CI: 50.88‐97.06] respectively). As specificity and negative predictive value had superior results than sensitivity and positive predictive value, rather than for diagnosis of this condition, MRI might be more considered for the follow‐up of patients with pulmonary mycosis, an alternative to multiple radiation exposures with CT follow‐up.